2018
DOI: 10.2340/16501977-2366
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hyaluronic acid after knee arthroscopy: A systematic review and meta-analysis

Abstract: Hyaluronic acid might be beneficial for patients after knee arthroscopy. However, the results remain controversial. A systematic review and meta-analysis was conducted to explore the efficacy of hyaluronic acid following knee arthroscopy. Randomized controlled trials assessing the effect of hyaluronic acid in knee arthroscopy were included. Compared with control intervention after knee arthroscopy, hyaluronic acid treatment was found to significantly improve Western Ontario and McMaster Universities Osteoarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Many factors can cause postoperative pain after arthroscopic surgery, and pain intensity is determined by the operation procedures. [24,25] For instance, arthroscopic anterior cruciate ligament reconstruction and meniscus repair result in postoperative pain at different levels. [6] The relief in postoperative pain is crucial for early postoperative rehabilitation and prevention of potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors can cause postoperative pain after arthroscopic surgery, and pain intensity is determined by the operation procedures. [24,25] For instance, arthroscopic anterior cruciate ligament reconstruction and meniscus repair result in postoperative pain at different levels. [6] The relief in postoperative pain is crucial for early postoperative rehabilitation and prevention of potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…Atay et al [ 33 ] evaluated HA injections after arthroscopic debridement surgery in KL grade 2-3 knee OA and at 12 mo follow-up; there was a significant difference found in WOMAC score changes between the arthroscopy with HA group and the arthroscopy without HA group. Finally, a more recent meta-analysis by Shen et al [ 34 ] showed that HA after arthroscopy was able to reduce pain on motion, indicating that HA is significantly associated with increased physical function and WOMAC score.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that while hyaluronan significantly improved WOMAC Osteoarthritis Index scores, there was no substantial improvement in pain scores at 2, 6, or 12 weeks post-arthroscopy. 58 ADDITIONAL RANDOMIZED CONTROLLED TRIALS Additional randomized controlled studies on hyaluronan have also been recently completed and were not considered in the previously discussed reviews and meta-analyses. Henrotin et al sought to further clarify and identify the biological and clinical biomarkers for the efficacy of Hymovis injections.…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%